Application of Computer Systems of Dynamic Modeling for Evaluation of Protection Behavior of Electric Power Lines - F. A. Romaniouk; I. V. Novash; А. A. Tishechkin; V. I. Roumiantsev; N. N. Bobko; E. V. Glinsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers problems pertaining to mathematical modeling of a transformer substation with protected electric power lines. It is proposed to use systems of dynamic modeling for investigations applying a method of calculative experiment with the purpose to evaluate behavior of protection and automation at short circuits. The paper contains comparison of results obtained with the help of program-simulated complex on the basis of a complex mathematical model of an object and with the help of dynamic modeling system – MathLab.